Interdecadal Linkage Between the Winter Northern Hemisphere Climate and Arctic Sea Ice of Diverse Location and Seasonality - He, Xulong; Zhang, Ruonan; Ding, Shuoyi; Zuo, Zhiyan (Frontiers in Earth Science, 2021)
During the past few decades, Arctic sea-ice has declined rapidly in both autumn and winter, which is likely to link extreme weather and climate events across the Northern Hemisphere midlatitudes. Here, we use reanalysis data to investigate the possible linkage between mid–high-latitude atmospheric circulation and Arctic sea-ice loss in different geographical locations and seasons and associated impacts on wintertime climate on interdecadal timescales. Four critical sea-ice subregions are analyzed in this study—namely, the Pan-Arctic, Barents–Kara–Laptev Seas (BKL), East Siberia–Chukchi–Beaufort Seas (EsCB), and Bering Sea (Ber). Results suggest that interdecadal reduction of autumn sea-ice, irrespective of geographical location, is dynamically associated with the negative phase of the North Atlantic Oscillation (NAO) in the subsequent winter via stratospheric pathways. Specifically, autumn sea-ice loss appears to cause a weakened stratospheric polar vortex that propagates to the troposphere in the ensuing months, leading to lower surface air temperature and a deficit in precipitation over Siberia and northeastern North America. Meanwhile, an anomalous cyclone over Europe favors excessive precipitation over southern Europe. For wintertime sea-ice loss in the Pan-Arctic and BKL, a weak positive NAO phase, with a dipole pressure pattern over Greenland–northeastern North America and North Atlantic, and a shrunken Siberian high over Eurasia are observed over mid–high-latitudes. The former results in excessive precipitation over northwestern and southeastern North America, whilst the latter leads to less precipitation and mild winter over Siberia. In contrast, Ber sea-ice loss is associated with a circumglobal wave train downstream of the Bering Sea, leading to extensive warming over Eurasia. The anomalous dipole cyclone and anticyclone over the Bering Sea transport more Pacific and Arctic water vapor to North America, and the anomalous cyclone over the Barents Sea results in abundant precipitation in Siberia. Such midlatitude anomaly is dynamically linked to winter sea-ice loss, mainly through tropospheric rather than stratospheric pathways. These results have important implications for future seasonal and interdecadal forecasts in the context of ongoing sea-ice decline.